2019
DOI: 10.1002/esp.4618
|View full text |Cite
|
Sign up to set email alerts
|

The transport of aggregates associated with soil organic carbon under the rain‐induced overland flow on the Chinese Loess Plateau

Abstract: Organic carbon (OC) is easily enriched in sediment particles of different sizes due to aggregate breakdown and selective transport for sheet erosion. However, the transport of aggregate‐associated OC has not been thoroughly investigated. To address this issue, 27 simulated rainfall experiments were conducted in a 1 m × 0.35 m box on slope gradients of 15°, 10°, and 15°and under three rainfall intensities of 45 mm h−1, 90 mm h−1 and 120 mm h−1. The results showed that OC was obviously enriched in sediment parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Despite the important influence of the transport of aggregates by erosion on associated carbon concentrations in different aggregate size classes this topic has not been thoroughly investigated. Liu et al (2019) reported that the SOC concentrations of each aggregate size class in sediments were different from those in the original soil and SOC was enriched in sediment particles of different sizes under sheet erosion.…”
Section: Particle Size Selectivity and Implication On Soil Carbon Poolsmentioning
confidence: 99%
“…Despite the important influence of the transport of aggregates by erosion on associated carbon concentrations in different aggregate size classes this topic has not been thoroughly investigated. Liu et al (2019) reported that the SOC concentrations of each aggregate size class in sediments were different from those in the original soil and SOC was enriched in sediment particles of different sizes under sheet erosion.…”
Section: Particle Size Selectivity and Implication On Soil Carbon Poolsmentioning
confidence: 99%
“…To the contrary, the stream power increased and quickly became stable with time, corresponding with the sediment loss rate. In this study, the high flow velocities have a positive exponential correlation with the transport number of >0.05 mm aggregates with high density and low OC concentration [ 16 , 17 ]. This is because the erosion is controlled by transport limitation.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, the OC mineralization potential of the sediments that can be deposited in low location may be large [ 48 , 49 ]. Under high runoff erosive power, that is, high flow velocity and stream power, the high sediment erosion rate ( Qs ) weakens the effect of aggregate stripping on uneven OC enrichment in sediments [ 16 ]. The OC mineralization potential of deposited sediments may be low because of the high soil erosion rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations